2008
DOI: 10.1128/aem.01185-08
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Expression and Subcellular Localization of the Aflatoxin Pathway Enzyme Ver-1 Fused to Enhanced Green Fluorescent Protein

Abstract: Aflatoxin, a mycotoxin synthesized by Aspergillus spp., is among the most potent naturally occurring carcinogens known. Little is known about the subcellular organization of aflatoxin synthesis. Previously, we used transmission electron microscopy and immunogold labeling to demonstrate that the late aflatoxin enzyme OmtA localizes primarily to vacuoles in fungal cells on the substrate surface of colonies. In the present work, we monitored subcellular localization of Ver-1 in real time in living cells. Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…Our previous data (3) strongly suggest that these vesicles are aflatoxisomes that carry aflatoxin and functional aflatoxin enzymes. In support of this idea, we previously observed that aflatoxin synthesis increases during a transition from active growth to stationary phase (24 to 36 h) (8). During this transition, the number of vesicles carrying the EGFP-tagged aflatoxin enzyme Ver-1 increased significantly (8) and these adhered to the inner surface of the cytoplasmic membrane.…”
Section: Resultssupporting
confidence: 51%
“…Our previous data (3) strongly suggest that these vesicles are aflatoxisomes that carry aflatoxin and functional aflatoxin enzymes. In support of this idea, we previously observed that aflatoxin synthesis increases during a transition from active growth to stationary phase (24 to 36 h) (8). During this transition, the number of vesicles carrying the EGFP-tagged aflatoxin enzyme Ver-1 increased significantly (8) and these adhered to the inner surface of the cytoplasmic membrane.…”
Section: Resultssupporting
confidence: 51%
“…There is evidence to suggest that many secondary metabolite biosynthetic pathways in fungi are restricted to specific organelles, as shown for cyclosporine, penicillin, and aflatoxin biosynthesis (51)(52)(53)(54)(55)(56). Recently specific synthesis vesicles, aflatoxisomes (57), were discovered in Aspergillus parasiticus.…”
Section: Discussionmentioning
confidence: 99%
“…The strains used in this study are listed in Table 1 : the model proposes that Nor-1 (early), Ver-1 (middle), and OmtA (late) are synthesized on free ribosomes in the cytoplasm, packaged into transport vesicles (6 -8), and transported to vacuoles via the cytoplasm-to-vacuole targeting (Cvt) pathway (6,8). In contrast Vbs localizes in the cytoplasm and in structures thought to be Golgi (29), suggesting it is transported to vacuoles via the classical secretory pathway; VBS is glycolsylated in support of this notion.…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that early (Nor-1), middle (Ver-1), and late (OmtA) aflatoxin enzymes localize in vesicles and vacuoles in A. parasiticus (6)(7)(8). To determine the functional role of these organelles in aflatoxin synthesis, a vesicle-vacuole fraction (V) was first isolated from A. parasiticus grown for 36 h in aflatoxin-inducing medium (YES) using a high-density sucrose cushion method.…”
Section: Vesicles and Vacuoles Are One Primary Site For The Late Stepmentioning
confidence: 99%
See 1 more Smart Citation